How a single personal revelation might not be a source of knowledge - Mawson, T (Cambridge University Press, 2003)
Many of those who come to a belief in the God of classical theism do so solely as a result of having had an experience which they believe it is reasonable for them to interpret as a revelation of His experience directly and graciously given to them by God Himself. I shall argue that - at least in the first instance - such people should probably not think of themselves as knowing that there is a God if they are also traditional libertarians and believe in Robert Nozick's theory of knowledge.